2016
DOI: 10.14238/sp7.2.2005.68-72
|View full text |Cite
|
Sign up to set email alerts
|

Ukuran Besar Testis Anak Laki-laki pada Saat Awitan Pubertas

Abstract: Latar belakang: data memperlihatkan terjadi perubahan usia awitan pubertas pada anak laki-laki dalam beberapa dekade belakangan ini. Hal ini mungkin disebabkan adanya perbaikan kondisi sosioekonomi, status gizi, kesehatan umum dalam jangka waktu tertentu tersebut. Perubahan tersebut mungkin juga mempengaruhi ukuran testis pada saat awitan pubertas anak laki-laki. Tujuan: untuk mengetahui gambaran besar testis anak laki-laki pada saat awitan pubertas. Metoda: penelitian cross sectional pada anak laki-laki di be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…17 A 2005 study in Indonesia found the mean age of pubertal onset to be 11-12 years. 18 A study in West Sumatera found a mean age of pubertal onset in boys from urban areas was lower than suburban areas [112.26 (SD 21.77 months vs. 119 (SD 19.65) months]. The mean age of pubertal onset in girls from urban areas is also lower than suburban areas [113.56 (SD 21.9) months vs. 115.6 (SD 18.78) months].4 This situation occurs due to differences in socioeconomic and nutrition conditions.…”
Section: Discussionmentioning
confidence: 99%
“…17 A 2005 study in Indonesia found the mean age of pubertal onset to be 11-12 years. 18 A study in West Sumatera found a mean age of pubertal onset in boys from urban areas was lower than suburban areas [112.26 (SD 21.77 months vs. 119 (SD 19.65) months]. The mean age of pubertal onset in girls from urban areas is also lower than suburban areas [113.56 (SD 21.9) months vs. 115.6 (SD 18.78) months].4 This situation occurs due to differences in socioeconomic and nutrition conditions.…”
Section: Discussionmentioning
confidence: 99%